Analysis of Student's Initial Counting Ability on Addition Material Using Abacus: Analisis Kemampuan Siswa Berhitung Permulaan Pada Materi Penjumlahan Menggunakan Sempoa - Ayu Fitriyanti Syawaliyah; Dwi Cahaya Nurani; Fahmi Surya Adikara (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2023)
This research aims to determine the factors that cause a child not to be able to add up basic addition operations which include the results of adding tens, hundreds and thousands in elementary school (SD) but not yet able to answer basic additions. So, the abacus media was chosen to help the process of understanding the basic operations of addition. This research is descriptive qualitative research with a case study approach. The research subject was a female student in class 3A at SD Negeri 002 Palembang for the 2022/2023 academic year with the initials ANA. The abacus used in this research is an ordinary type of abacus whose bead value is a multiple of 10. Each row of beads has 10 beads up to the 10th row with a total of 100 beads. The results of the research show that the abacus is closely related to developing numeracy skills, supported by the knowledge of a child or student who already knows place value in initial counting, especially addition operation material.